Technological aspects of creation of nitrided discrete coatings with using laser processing - Іщук, Наталія Володимирівна; Кіндрачук, Мирослав Васильович; Писаренко, Володимир Миколайович (Eastern-European Journal of Enterprise Technologies, 2013)
The results of studying wear-resistant nitrided coatings of steels by combined laser and chemical-thermal processing are given in the paper. A new approach to design and formation of discrete nitrided coatings was formulated and implemented, based on purposeful use of structural-phase state of steels after previous laser treatment, which determines qualitative and quantitative changes in the nitrided layer. The regularities of the influence of previous laser processing in quenching and doping modes on phase and chemical composition, structure and properties of nitrided layers on steels were established. Increased solubility of nitrogen after laser treatment is the result of defect structure. The influence of secondary structural heterogeneity of the surface, formed by discrete laser treatment, on wear resistance was investigated. It was established that previous laser processing significantly accelerates diffusion processes of nitriding, increases microhardness and changes phase composition compared with traditional nitriding methods. Experimental studies allowed establishing regularities of the influence of parameters of discrete structure, stress-strain state, surface nitrogen concentration, phase composition, microhardness of modified surface on its wear resistance. It is shown that discrete laser treatment improves wear resistance of steel 40X twice, continuous nitriding by 2.8 times and discrete nitriding by 5.6 times.